Síntese, caracterização e propriedades magnéticas de Ferritas de níquel – cobre - Sorrentino Neto, Antônio (2016)
The ceramic oxides that exhibit ferromagnetic behavior are important commercial products for electronics industries and are commonly known as ferrites. In this work, we synthesized different compositions of CuxNi1-xFe2O4 ferrite with x = 0,0, 0,2, 0,4, 0,6, 0,8 and 1,0 by using the combustion method starting from the iron nitrate, nickel and copper and urea as a reducing agent. The powders were characterized by determination of specific surface area by the method (BET), X-ray diffraction (XRD), refinement of XRD data by the Rietveld method and vibrating sample magnetometry (MAV). The obtained copper nickel ferrites, referring x = 0,0, 0,2, 0,4, 0,6 synthesized had the same number of peaks corresponding to the single phase-forming powders that have been indexed to the spinel ferrite phase, forming a cubic phase and x = 0,8 to 1,0 tetragonal phase formed enhancing the efficiency of the applied method of synthesis. The refinement by the Rietveld method resulted in a determination of cell parameter of the samples, the cubic phase the value 0.8359 to 0.8340 nm and the crystallite size whose values occur between 239.62 to 187.24 nm. While in the tetragonal phase the cell parameter a = b was 5.8253 to 5,8230nm c = 8.5693 to 8.6941 nm. The hysteresis curves showed magnetic materials profile. The nickel ferrite - synthesized copper proved as materials with high potential for applicability in different areas of high-frequency devices such as phones and components for computers.